anonymous
  • anonymous
solve by substitution 3x-2y=5 4x-5y=2
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
.Sam.
  • .Sam.
3x-2y=5 4x-5y=2 -------------------------------------------- 3x-2y=5 x=(5+2y)/3 --------------------------------------------- 4x-5y=2. 4(5+2y)/3-5y=2 (4(5+2y))/(3)-5y=2 (4(2y+5))/(3)-5y=2 (4(2y+5))/(3)-5y*(3)/(3)=2 (4(2y+5))/(3)-(15y)/(3)=2 (4(2y+5)-(15y))/(3)=2 (-7y+20)/(3)=2 -7y+20=6 -7y=-14 y=2 ------------------------------------------ x=(5+2y)/3 x=(5+2(2))/3 x=3
anonymous
  • anonymous
pick either equation and solve for either x or y then use the expression created (for example x=blah) to substitute in the other equation) x+2y=0, will become blah+2y=0 to get the first expression created for x=blah you will eliminate every x, since the only x you can get is the first one in x=... hence you will be left with an equation containing only y and you can solve for y

Looking for something else?

Not the answer you are looking for? Search for more explanations.